KAJIAN YURIDIS TUNTUTAN GANTI RUGI ATAS PELANGGARAN HAK CIPTA DALAM KARYA SINEMATOGRAFI - TRISADHEA AZZAHRA NIM. A1011191295 (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstractThe current development of the film industry in Indonesia has not been spared from film piracy elements, the current technological advancement factor means that film piracy is not done by recording and inserting it on a CD and then selling it freely on the market but by downloading and uploading films. -the film uses various electronic media and is then shown on unofficial online film sites. For this reason, it is necessary to take action from the Creator, Copyright Holder and Related Rights Holder regarding this action, such as a claim for compensation for the losses experienced. The first aim of this research is to analyze the efforts that can be made by creators, copyright holders and related rights holders for copyright infringement in cinematographic works. Second, to analyze the resolution of exclusive rights that have been violated by copyright infringers. This research uses normative methods. Normative legal research is legal research that places law as a building system of norms. The norm system that is built is about principles, norms, rules from laws and regulations, court decisions, agreements, and doctrines (teachings). Normative legal studies see the relationship between legal events and legal rules or regulations as a system. Copyright holders can sue for compensation for copyright infringement in cinematographic works, especially if it has legal force that the perpetrator is proven guilty by a criminal decision. There are 3 (three) laws and regulations that regulate copyright infringement of cinematographic works, and film piracy, namely; Law Number 28 of 2014 concerning Copyright, Law Number 33 of 2009 concerning Films, and Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions.Keywords: Copyright, Piracy, Cinematographic WorksAbstrak Berkembangnya industri perfilman di Indonesia saat ini tak luput dari oknum-oknum pembajakan film, faktor kemajuan teknologi di masa kini menyebabkan pembajakan film tak dilakukan dengan cara merekam dan memasukkannya ke dalam sebuah CD dan kemudian di jual bebas di pasaran melainkan dengan cara mengunduh dan mengunggah film-film tersebut menggunakan berbagai media elektronik dan kemudian ditayangkan pada situs-situs film online tidak resmi. Untuk itu perlu adanya tindakan dari Pencipta, Pemegang Hak Cipta, dan Pemegang Hak Terkait atas tindakan tersebut seperti tuntutan atas ganti kerugian yang dialami. Tujuan penelitian ini pertama, adalah untuk menganalisis upaya yang dapat dilakukan oleh pencipta, pemegang hak cipta, dan pemegang hak terkait atas pelanggaran hak cipta dalam karya sinematografi. Kedua, Untuk menganalisis penyelesaian atas hak eksklusif yang telah dilanggar oleh pelaku pelanggaran hak cipta. Peneliatan ini menggunakan metode normatif. Penelitian hukum normatif adalah penelitian hukum yang meletakkan hukum sebagai sebuah bangunan sistem norma. Sistem norma yang dibangun adalah mengenai asas-asas, norma, kaidah dari peraturan perundangan, putusan pengadilan, peranjian, serta doktrin (ajaran). Studi hukum normatif melihat hubungan peristiwa hukum dengan aturan atau peraturan hukum sebagai sistem. Pemegang Hak Cipta dapat menuntut gugatan ganti rugi atas pelanggaran hak cipta dalam karya sinematografi, terlebih jika sudah memiliki kekuatan hukum bahwa pelaku terbukti bersalah dengan putusan pidana. Terdapat 3 (tiga) Peraturan Perundang-Undangan yang mengatur mengenai pelanggaran hak cipta karya sinematografi pembajakan film yaitu; Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta, Undang-Undang Nomor 33 Tahun 2009 Tentang Perfilman, dan Undang-Undang Nomor 19 Tahun 2016 Tentang Perubahan Atas Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik.Kata Kunci: Hak Cipta, Pembajakan, Karya Sinematografi